The androgen receptor is significantly associated with vascular endothelial growth factor and hypoxia sensing via hypoxia-inducible factors HIF-1a, HIF-2a, and the prolyl hydroxylases in human prostate cancer - Boddy, Jane L; Fox, Stephen B; Han, Cheng; Campo, Leticia; Turley, Helen; Kanga, Suresh; Malone, Peter R; Harris, Adrian L (Clinical cancer research, 2005)
Hypoxia regulates key biological processes including angiogenesis via the transcription factor, hypoxia-inducible factor (HIF). In prostate cancer, angiogenesis is also influenced by androgens, and recent cell line studies suggest that this effect is partly mediated by HIF. The study aimed to assess whether a relationship exists in human prostate cancer between expression of the androgen receptor, HIFs, and the key angiogenesis factor, vascular endothelial growth factor (VEGF). A tissue microarray comprised of 149 radical prostatectomy specimens was constructed. Semiquantitative immunohistochemical analysis was used to assess the expression of the androgen receptor, VEGF and HIF-1a and 2a, and their regulatory prolyl hydroxylase enzymes (PHD1, PHD2, and PHD3). Statistical analysis compared these factors with each other and with prostate-specific antigen relapse. There was a significant correlation between HIF-1a and HIF-2a expression (P = 0.02), and with androgen receptor (P = 0.04 and P < 0.001, respectively) and VEGF expression (P = 0.05 and P < 0.001, respectively). VEGF was also significantly related to the androgen receptor (P = 0.05), whereas PHD2 was inversely related to HIF-2a expression. No significant association was shown between HIF-1a or HIF-2a and time to prostate-specific antigen recurrence (P = 0.20 and P = 0.94, respectively). These findings confirm the relationship between hypoxia and the androgen receptor in prostate cancer, and show for the first time, the role of HIF-2a in this disease process. They provide clinical evidence to support the recent cell line findings that androgens may regulate VEGF levels through the activation of HIF in androgen-sensitive tumors. Inhibition of both the HIF pathways may provide new therapeutic options in the management of this disease.